“Speech Delay” Phenomenon and Its Influencing Factors - Rosa Akhirunnisa; Malida Fatimah (International Journal Labs, 2025)
Speech delay is one of the developmental disorders that often occurs in early childhood. This phenomenon can have a significant impact on children's communication and social aspects. This study aims to analyze the causative factors, impacts, and effective intervention strategies in dealing with speech delay through a literature review approach. The method used involves searching and critically analyzing various relevant scientific sources. The results of the study show that environmental, biological, and psychosocial factors play a role in the occurrence of speech delay. Early intervention involving the active role of parents and professionals has been proven to be effective in overcoming speech delays in children.